Analisa Yuridis Keterlambatan Pembayaran Manfaat Asuransi Jiwa PT. Asuransi Jiwasraya - Ghanisworo Ayu Pratiwi; Mas Anienda Tien Fitriyah (Universitas Widya Gama Malang, 2022)
This study aims to analyze the causes of non-fulfillment of life insurance benefit payments at PT. Asuransi Jiwasraya in the perspective of positive law that applies in Indonesia and the efforts taken by PT. Asuransi Jiwasraya in late payment of life insurance benefits. This study uses a normative juridical research method, where the legal problems that occur will be analyzed by the authors using a statutory approach and literature study. The results of this study indicate PT. Asuransi Jiwasraya does not fulfill the benefits of its customers, because it shows that they are in default on the policy agreement that has been agreed upon by PT. Asuransi Jiwasraya with customers, because of their carelessness in investing customer money which resulted in customers failing to get the benefits. The responsibilities carried out by PT. Asuransi Jiwasraya in accordance with the PT. Asuransi Jiwasraya with customers that if there is a dispute, the settlement will be carried out through deliberation, mediation, reporting to the OJK, legal channels or the courts. The settlement efforts did not result in deliberation, failed mediation and no administrative sanctions were imposed by the OJK, and there were also no claims for default from the courts. There is no dispute resolution contained in the policy agreement that brings results to get customer benefits. The solution from the author should be if PT. Asuransi Jiwasraya cannot pay the benefits directly, it can be done in stages with the customer's approval.